Synthesis, Structure, and Physical Properties for a Series of Trigonal Bipyramidal M(II)–Cl Complexes with Intramolecular Hydrogen Bonds - Sickerman, Nathaniel S. (2012)
A series of transition metal chloro complexes with the tetradentate tripodal tris(2-amino-oxazoline) ligand TAO have been synthesized and characterized. X-ray structural analyses of these compounds demonstrate the formation of the mononuclear complexes [M(II)(TAO)(Cl)](+), where M(II) = Cr, Mn, Fe, Co, Ni, Cu and Zn. These complexes exhibit distorted trigonal-bipyramidal geometry, coordinating the metal through an apical tertiary amine, three equatorial imino nitrogen atoms, and an axial chloride anion. All the complexes possess an intramolecular hydrogen-bonding (H-bonding) network within the cavity occupied by the metal-bound chloride ion. The metal-chloride bond distances are atypically long, which is attributed to the effects of the H-bonding network. Nuclear magnetic resonance (NMR) spectroscopy of the Zn complex suggests that the solid-state structures are representative of that observed in solution, and that the H-bonding interactions persist as well. Additionally, density functional theory (DFT) calculations were carried out to probe the electronic structures of the complexes.